ANALYSIS OF QUR'AN MEMORIZATION LEARNING USING THE TALAQQI METHOD AT MI DARUL ISHLAH: EVALUATION AND CHALLENGES - Zuhri, Zuhri; Salam, Salam; Sumaryati, Sumaryati (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: The memorization of the Qur'an (Tahfidz) plays a central role in Islamic education, as it fosters a deep connection with the text and its values. In recent years, the Talaqqî method has gained attention as an effective approach to Qur'anic memorization, particularly in educational institutions. However, its implementation faces several challenges, especially in formal school settings. Purpose: This study aims to analyze the implementation of Qur'an memorization using the Talaqqî method at MI Darul Ishlah in Lubuklinggau. Method: With a focus on evaluating the process and identifying key challenges, this research employs a qualitative approach with a descriptive-analytical design. Result: The findings reveal that the Qur'an memorization program is organized in three main stages: planning, implementation, and evaluation. Planning includes selecting qualified teachers and developing memorization strategies tailored to the students' varied abilities, many of whom are at the initial stages of Quranic literacy. During the implementation phase, teachers recite verses for students to repeat, ensuring proper memorization under direct guidance. The evaluation process, conducted at the end of each semester, assesses students' progress and identifies challenges, such as time constraints and diverse learning abilities. Conclusion: Despite the success of the program, several challenges remain, notably the need to improve teacher expertise in the Talaqqî method and to increase parental involvement to enhance the effectiveness of the memorization process.